ANALYSIS OF THE MESSAGE OF CHILDRENS STORIES BY PGMI STUDENTS AS AN ALTERNATIVE LITERATURE LEARNING MATERIAL IN ELEMENTARY SCHOOLS - Beby Dwi Febriyanti (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the moral messages contained in children’s stories written by students of the Madrasah Ibtidaiyah Teacher Education (PGMI) program as an alternative literary learning material in elementary schools. This research employed a descriptive qualitative approach with data drawn from children’s story manuscripts written by 10 third-semester PGMI students at the Islamic University of Jember. The analysis focused on narrative passages and dialogues containing moral values, using Miles and Huberman’s model of data reduction, display, and conclusion drawing. The results show that all student-created stories included moral messages that are appropriate as role models for pupils. The messages were conveyed both explicitly and implicitly, encompassing character values such as honesty, responsibility, religiosity, hard work, and gratitude. These findings suggest that PGMI students’ literary works can serve as alternative teaching materials that are contextual, engaging, and relevant for fostering positive character development in elementary students. Thus, student-created children’s stories not only act as a medium of creative expression but also contribute significantly to character education and literacy in primary schools.